Soil and crop management systems that ameliorate damage caused by decades of dryland agroecosystem mismanagement. (23rd May 2020) - Peterson, G. A.; Westfall, D. G.; Schipanski, M. E.; Fonte, S. J.
Abstract: Sustainable crop production in the Great Plains of North America has been challenging since early settlement times, and mismanagement has severely damaged our dryland agroecosystems. The unintentional damage stemmed from using practices unsuited to dryer climates. In fact, the management practices imported from more humid agricultural areas during the settlement period were considered the best ways to farm. The Dust Bowl era was the disastrous result of creating bare soil surfaces, with aggregates pulverized by excessive tillage on millions of hectares of land. It became obvious to pioneer scientists that retaining cover on the soil surface was critical to sustainability and their early efforts resulted in a widely adopted practice known as stubble mulch. Stubble mulch practices markedly decreased the rate of damage to dryland ecosystems. Advent of herbicidal weed control led to reduced and no‐till practices that not only increased soil cover, but also significantly enhanced soil water conservation. This paper focuses on how and why the coupling of conservation tillage and cropping intensification is ameliorating the damage that accrued over decades of agroecosystem mismanagement. The objectives of this paper are to (a) remind us of fragile nature of the Great Plains ecosystem, (b) review how and why ecosystems were degraded, and (c) identify principles and associated practices for amelioration.